5 Investigating the effect of catecholamines on ischaemia-induced ventricular fibrillation when in the presence of an intraventricular balloon. (December 2018) - Pickles, William; Curtis, Michael
Abstract : Introduction: Sudden cardiac death (SCD) is the greatest cause of cardiovascular disease-related mortality. Lethal ventricular fibrillation (VF), arising from myocardial infarctions is the most prominent cause of SCD. The isolated rat heart is widely used to model ischaemia-induced VF owing to its ability to produce high baseline incidences of VF and the ability to regulate several known arrhythmogenic mediators. A model that allows concurrent assessment of VF and contractile function would halve animal requirements. Unfortunately, in Langendorff perfused rat hearts, IVB inflation inhibits the ability of regional ischaemia to elicit VF. 1 However, perfusion with catecholamines facilitates ischaemia-induced VF (I-IVF) in IVB-free hearts when risk of VF is low due to a small ischaemic territory. 2 Therefore, it was sought to overcome the IVB-induced VF suppression by perfusion with exogenous catecholamines: rendering a model in which the antiarrhythmic properties and the effects on heart dynamics a potential drug has could be assessed simultaneously. Here we tested whether catecholamines can surmount the antiarrhythmic effect of IVB inflation. Methods: Male Wistar rat (285–400 g) hearts were Langendorff-perfused with an IVB positioned in the left ventricle and minimally inflated (0.01 ml) to give a detectable developed pressure (˜30 mmHg; 'IVB' groups) or inflated substantially (0.12 ml) to give a developed pressure >100 mmHg ('IVB inflated'). Baseline assessment (−11 min) during perfusion with Krebs' (modified to contain 4 mM K + ) was followed by randomized and blinded switch to test solution at −10 min, then left coronary artery ligation at time zero, with ischaemia maintained for 60 min. Test solution comprised Krebs' containing catecholamines (93.9 nM noradrenaline and 22.5 nM adrenaline in 15 mM ascorbate vehicle) or vehicle alone (n=9/group). Design (blinded and randomized) and data analysis (e.g. use of ANOVA for Gaussian-distributed data and Fisher's exact test for VF incidence) accorded with BPS guidelines. 3 Results: Heart rate and developed pressure were increased by catecholamines (Cat) from 1 min before ligation (−1 min) (294±6, 310±13 to 437±10, 442±13 Beats/min and 28±2, 101±3 to 94±14, 177±10 mmHg for IVB and IVB inflated groups respectively), and the effect on pressure was exacerbated by IVB inflation (IVB 30±3 mmHg vs IVB inflation 101±3 mmHg). Ischaemia reduced developed pressure, with effects sustained during ischaemia. Mean ischaemic zone size varied between groups from 53±2 to 59%±1% (p>0.05). Cats increased VF incidence (Vehicle 0% vs Cats 56%) (p<0.05) and extended the susceptibility time window past 30 min of ischaemia, but IVB inflation was antiarrhythmic during ischaemia and surmounted the arrhythmia facilitating effect of catecholamines (IVB inflated +CATs 0% vs IVB +Cats 56%). Conclusion: Catecholamine perfusion was unable to surmount IVB-induced VF suppression. Unfortunately this rendered VF incidence too low to permit the assay to be suitable for evaluating drug effects on VF and contractile function contiguously. References: Wilder CDE, et al . Br J Pharmacol 2016;173:39–52. Wilder CDE, et al . 2016. http://www.pa2online.org/abstracts/vol13issue3abst245p.pdf Curtis MJ, et al . Br J Pharmacol 2015;172:2671–2674.